LO51: Emergency department use by pregnant women: a population-based study within a universal healthcare system. (May 2020) - Varner, C.; Park, A.; Little, D.; Ray, J.
Abstract : Introduction: Emergency Department (ED) utilization during pregnancy may be common, but data specific to universal healthcare systems like Canada are lacking, where pregnancy care is supposed to be standardized. The objective of this study was to quantify and characterize ED utilization among all Ontarian women who had a recognized pregnancy, including by trimester and within 42 days after pregnancy, and further stratified by pregnancy outcome. Methods: Utilizing provincial administrative health databases, this retrospective population-based cohort study included all recognized pregnancies in Ontario conceived between April 1, 2002 and March 31, 2017. Peri-pregnancy ED utilization was defined as any ED visit from 0-42 weeks' gestation, or within 42 days after the end of pregnancy. Modified Poisson regression was used to generate relative risks (RR) and 95% confidence intervals (CI) for the outcome of any peri-pregnancy ED utilization in association with maternal characteristics. Results: Peri-pregnancy ED utilization occurred among 1, 075, 991 of 2, 728, 236 recognized pregnancies (39.4%), including among 35.8% of livebirths, 47.3% of stillbirths, 73.7% of miscarriages, and 84.8% of threatened abortions. There were 22, 802 (0.84%) ectopic pregnancies among all pregnancies in the cohort. ED utilization peaked in the first trimester and in the first week postpartum. A dose-response effect was seen in the number of peri-pregnancy ED visits in relation to certain maternal characteristics. Women residing in rural areas had an odds ratio (OR) of 3.44 (95% CI 3.39 to 3.49) for ≥ 3 ED visits, compared to those in urban areas. Women with 3-5 (OR 1.99 95% CI 1.97-2.01), 5-6 (OR 3.55, 95% CI 3.49 to 3.61), or ≥ 7 (OR 7.59, 95% CI 7.39 to 7.78) pre-pregnancy comorbidities were more likely to have ≥ 3 peri-pregnancy ED visits than those with 0-2 comorbidities. Of all recognized pregnancies in the cohort, only 106, 989 (3.9%) had an injury-related ED visit. Conclusion: Peri-pregnancy ED utilization occurs in nearly 40% of pregnancies, notably in the first trimester and immediately postpartum. Efforts are needed to streamline rapid access to ambulatory obstetrical care during these peak periods, when women are vulnerable to either a miscarriage, or a complication after a livebirth.